INFLUENCE OF BRAND LOYALTY ON CONSUMER SATISFACTION TOWARDS SPORTSWEAR (FUTSAL SHOES) - Lodjo, Riefaldo Akwila; Tumewu, Ferdinand (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2015)
Sportswear has become a common and popular category among young people as it identifies them with a more relaxed lifestyle, greater versatility and comfort. Many companies, especially those in the sportswear industry try to enhance brand loyalty among their customers. The purposes of this research is to know the impact of brand loyalty of sportswear based on customer satisfaction on marketing. This research use quantitative research with Multiple Regressions analysis method by using validity and reliability test to measure the data that had been gathered by the questtionnaire. The result shows that Brand Name, Product Quality, Product Style, and Product Promotion influence have significant impact on Consumer satisfaction towards futsal shoes simultaneously.The marketers of sport wear products must consider about the importance Brand Name, Product Quality, Product Style and Product Promotion, regarding with it in advanced. On the other hand, the owner of sport wear products must also evaluate other important factors that affect the consumer satisfaction in regard to the continuity of the business in the future. Keywords: brand name, product quality, product style, product promotion, consumer satisfaction